Aerobic Exercise Prescription in Stroke Rehabilitation: A Web-Based Survey of US Physical Therapists. Issue 2 (April 2017) - Boyne, Pierce; Billinger, Sandra; MacKay-Lyons, Marilyn; Barney, Brian; Khoury, Jane; Dunning, Kari
Abstract : Background and Purpose: Best practice recommendations indicate that aerobic exercise (AEX) should be incorporated into stroke rehabilitation. However, this may be challenging in clinical settings. The purpose of this study was to assess physical therapist (PT) AEX prescription for patients with stroke, including AEX utilization, barriers to AEX prescription, dosing parameters, and safety considerations. Methods: A cross-sectional Web-based survey study was conducted. Physical therapists with valid e-mail addresses on file with the state boards of Florida, New Jersey, Ohio, Texas, and Wyoming were eligible to participate. Survey invitations were e-mailed to all licensed PT in these states. Analysis focused on respondents who were currently involved with clinical stroke rehabilitation in common practice settings. Results: Results from 568 respondents were analyzed. Most respondents (88%) agreed that AEX should be incorporated into stroke rehabilitation, but 84% perceived at least one barrier. Median prescribed AEX volume varied between practice settings from 20- to 30-minute AEX sessions, 3 to 5 days per week for 2 to 8 weeks. Prescribed intensity was most commonly light or moderate; intensity was determined by the general response to AEX and patient feedback. Only 2% of respondents reported that the majority of their patients with stroke had stress tests. Discussion and Conclusions: Most US PTs appear to recognize the importance of AEX for persons poststroke, but clinical implementation can be challenging. Future studies and consensus are needed to clarify best practices and to develop implementation interventions to optimize AEX utilization in stroke rehabilitation. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A167 ). Abstract : Supplemental Digital Content is Available in the Text.